Bilibid and beyond: Race, body size, and the native in early American colonial Philippines. (15th October 2018) - Gealogo, Francis A.
Abstract : The United States' occupation of the Philippines began with proclamations of a new era of development and the prospect of local political representation. In coming to grips with what they saw as America's civilising mission, colonial scholars and officials sought information about the peoples of the Philippines by conducting a census and various population studies, using an array of methodologies drawn from criminology and physical anthropology. This article traces and critiques representations of the Philippine population in the 1903 Philippine Census as well as in several related studies published in the early American period, which served to reduce the Filipinos to a state of 'otherness' which served to justify colonial projects. Several of these racialised studies used the inmates of Bilibid Prison, both alive and dead, as experimental and documentary subjects to create a record of Filipino 'sample types' for various administrative and other purposes, such as the exhibition at the St Louis World's Fair of 1904. Bilibid prisoners' body size, brain weight, skin colour, facial features and other physical attributes were selectively correlated with other colonial constructions of Filipino individuals and groups, such as 'wildness' and political maturity.